2022
DOI: 10.1021/acs.nanolett.1c04425
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Synergistic Effect of Heteroatomic Substitution and Vacancy Engineering in CoFe2O4 for Superior Electrocatalysis Performance

Abstract: Metal ion substitution and anion exchange are two effective strategies for regulating the electronic and geometric structure of spinel. However, the optimal location of foreign metallic cations and the exact role of these metals and anions remain elusive. Herein, CoFe2O4-based hollow nanospheres with outstanding oxygen evolution reaction activity are prepared by Cr3+ substitution and S2– exchange. X-ray absorption spectra and theoretical calculations reveal that Cr3+ can be precisely doped into octahedral (Oh)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(49 citation statements)
references
References 37 publications
3
44
0
Order By: Relevance
“…Significantly, the pre-edge peak of Mn 10 -doped CoP (Figure S8) shifted to a higher energy than that of CoP, indicating that the Co oxidation state in Mn 10 -doped CoP is higher. 62 These near-edge absorption spectra were also consistent with the results of XPS, further indicating that Mn doping can regulate the electronic structure of the Co atom. In the Fourier transform curves of Mn 10 -doped CoP and CoP (Figure 4b), there is almost no change in the Co−P bond length (about 1.78 Å) after doping, possibly due to the similar ionic radius of the substitutional dopant and low content of doped metal.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Significantly, the pre-edge peak of Mn 10 -doped CoP (Figure S8) shifted to a higher energy than that of CoP, indicating that the Co oxidation state in Mn 10 -doped CoP is higher. 62 These near-edge absorption spectra were also consistent with the results of XPS, further indicating that Mn doping can regulate the electronic structure of the Co atom. In the Fourier transform curves of Mn 10 -doped CoP and CoP (Figure 4b), there is almost no change in the Co−P bond length (about 1.78 Å) after doping, possibly due to the similar ionic radius of the substitutional dopant and low content of doped metal.…”
Section: Resultssupporting
confidence: 80%
“…Co K-edge spectra of Mn 10 -doped CoP are similar to those of CoP (Figure a). Significantly, the pre-edge peak of Mn 10 -doped CoP (Figure S8) shifted to a higher energy than that of CoP, indicating that the Co oxidation state in Mn 10 -doped CoP is higher . These near-edge absorption spectra were also consistent with the results of XPS, further indicating that Mn doping can regulate the electronic structure of the Co atom.…”
Section: Resultssupporting
confidence: 76%
“…The number of electrons transferred by VS 2 /rGO for the reduction of each oxygen molecule was therefore, found to be 3.98 (Figure 4d) from 0.1 to 0.5 V, which is much superior compared to VS 2 (Figure S10b) or rGO (Figure S10d) and even slightly better than commercial Pt/C (Figure S10f). The calculated n av values for VS 2 , rGO, VS 2 /rGO and commercially available Pt/C are 2.13, 2.88, 3.98 and 3.92, respectively in the same potential range, signifying the growth of both H 2 O 2 and H 2 O (probable mechanistic pathway has been provided in Supporting Information) [52,53] though, the amount of H 2 O 2 formation gradually decreases for the composite VS 2 /rGO. This result matches well with RRDE (Figure5b, S11b), which further demonstrates negligible H 2 O 2 formation (FigureS11a and 5c) on the disk electrode surface, indicating beneficial and synergistic contribution of VS 2 to rGO towards ORR reaction.…”
Section: Probable Mechanism and Factors Affecting The Orr Activitymentioning
confidence: 93%
“…[24][25][26] For instance, Sun et al reported a simple method to introduce Cr 3 + into CoFe 2 O 4 hollow nanospheres and simultaneously induce Co vacancies, which promote excellent OER activity. [27] Therefore, the underlying construction of nano-catalysts with fine morphologies, defects, and interfacial structures is crucial for enlarging the specific surface area, enriching active sites, enhancing electronic conductivity, facilitating ion mass transfer, shortening electrolyte diffusion distance, and ultimately improving electrocatalytic performance. [28][29][30] Here, inspired by the advantages of defect engineering (heteroatom doping and oxygen vacancies), we have adopted a simple reflux method to design porous g-C 3 N 4 lamellar with Ndoped carbon, and reported a facile protocol for the synthesis of sandwich-like g-C 3 N 4 /NiCo 2 O 4 heterostructure.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Sun et al. reported a simple method to introduce Cr 3+ into CoFe 2 O 4 hollow nanospheres and simultaneously induce Co vacancies, which promote excellent OER activity [27] . Therefore, the underlying construction of nano‐catalysts with fine morphologies, defects, and interfacial structures is crucial for enlarging the specific surface area, enriching active sites, enhancing electronic conductivity, facilitating ion mass transfer, shortening electrolyte diffusion distance, and ultimately improving electrocatalytic performance [28–30]…”
Section: Introductionmentioning
confidence: 99%